Further investigation of the HEXA gene intron 9 donor splice site mutation frequently found in non-Jewish Tay-Sachs disease patients from the British Isles. - Landels, E C (1993)
In a previous study we found that a Tay-Sachs disease (TSD) causing mutation in the intron 9 donor splice site of the HEXA gene occurs at high frequency in non-Jewish patients and carriers from the British Isles. It was found more frequently in subjects of Irish, Scottish, and Welsh origin compared with English origin (63% and 31% respectively). We have now tested, in a blind study, 26 American TSD carriers and 28 non-carriers who have British ancestry for the intron 9 splice site mutation. Six of the carriers and none of the controls were positive for the mutation. All six had Irish ancestry, compared with nine of the 20 other (intron 9 mutation negative) TSD carriers (p < 0.05). These results confirm the previously found high frequency of the intron 9 mutation in non-Jewish TSD families of British Isles, particularly Irish, origin, and reinforce the need to screen such families for this mutation.